The effect of cigarette smoking upon hematological adaptations to moderately high altitude living - Ramirez, G.; Bittle, P.A.; Colice, G.L.; Herrera, R.; Agosti, S.J.; Foulis, P.R. (Journal of Wilderness Medicine, 1991)
Life at moderately high altitude (3000 m) involves physiological adaptations to chronic hypoxemic conditions. We studied hematological adaptations to high altitude living, the effect of cigarette smoking on this adaptation, and the relation of pulmonary function to these changes. Higher red blood cell counts, hemoglobin and hematocrit, and lower mean corpuscular volumes were found in high altitude dwellers (p < 0.05). Smoking at high altitude was associated with a further increase in hemoglobin and hematocrit and a higher mean corpuscular volume and mean corpuscular hemoglobin concentration than in non-smoking high altitude subjects. Plasma erythropoietin levels were significantly higher (p < 0.05) in high altitude dwellers compared to sea level inhabitants, although no difference was observed between smokers and non-smokers at the same altitude. Erythropoietin concentration was totally independent of pulmonary function and oxygen saturation in both high altitude and sea level subjects. Spirometric results were similar in age matched nonsmoking subjects at high altitude and sea level. Smoking was associated with a reduction in the predicted forced expiratory flow at sea level but not at high altitude.